Responsiveness of the Brazilian broadcasting regulatory system of sanctions (Law, State and Telecommunications Review, 2016)
Purpose ”“ The purpose of this paper is to evaluate the responsiveness of the system of sanctions applicable to broadcasting concessionaires in Brazil.Methodology/approach/design ”“ The research considered the theory of responsive regulation proposed by Ayres and Braithwaite as parameter for the critical analysis of the Brazilian broadcasting regulatory system of sanctions.Findings ”“ The research concluded that the system of sanctions does not encourage concessionaires to comply with its legal, contractual and regulatory obligations, as penalties do not promote dialogue between regulator and regulated firms. There are legal obstacles for the application of the maximum penalty of revocation of concession, and some fines imposed on concessionaires in the past could not be collected as they were barred by statute of limitations.Practical implications ”“ The findings of this research may be considered by Brazilian regulators on the development of a more responsive and effective system of sanctions for broadcasting.Originality/value (optional) ”“ The research introduces the discussion on responsiveness regarding the Brazilian broadcasting regulatory model.